Multidisciplinary Management of Patient with Hypodontia and Transposed Mandibular Canines: A Case Report - Joshi, Pramod; Hegde, Nilesh; Bhat, Sudhakar (Orthodontic Journal of Nepal, 2012)
A multidisciplinary approach is generally required in the treatment of patients who presents with missing and malpositioned teeth to achieve a long term esthetic and functional result. Treatment of a patient with hypodontia and congenitally transposed mandibular canines using a multidisciplinary approach is presented.